Examining Governing Board Functions and Health Center Performances During Health System Reform: A Cross-sectional Study in 4 Regional States of Ethiopia - Mesele Damte Argaw; Binyam Fekadu Desta (Kerman University of Medical Sciences, 2022)
BackgroundSince 1995, the Ethiopian health system has been managed through decentralizing functions, resources, and authorities to local levels. As a result, health centers are led and managed by governing boards. In addition, the national health system strives to transform the performance of health centers through the implementation of reforms. Therefore, this study aims to examine the relationship between governing board functions and health center performances within a health reform context in 4 agrarian regions of Ethiopia. MethodsA cross-sectional survey was conducted from August 28, 2018 to September 30, 2018. Primary data were collected from governing board chairpersons or their designees using interviewer-administered structured questionnaires. The performance of each health center was rated out of 100 percentage points against the Ethiopian Health Center Reform Guideline (EHCRIG) standards. Secondary data were abstracted from a routine health information database using customized tools to capture achievements on 69 EHCRIG standards and its 174 validation criteria. Since the data violate the assumptions of the parametric test, the Spearman's rank (rho) correlation test, (a non-parametric test) was employed to see if any correlation exists among 4 parameters; namely: structure, roles and responsibilities, training and development of governing boards, and performance of health centers against EHCRIGs standards. A statistically significant relationship was claimed at P < .050. ResultsAll 83 health center governing boards or designees who were approached for this study, participated. The mean health center governing board function score with standard deviation was 56.0% (SD ± 14.5%). The overall performance of health centers against EHCRIGs was 70.4% (SD ± 15.0%). There was a statistically significant and strong correlation (Spearman rho correlation coefficient) between health center performance scores measured against reform standards with governing board scores of (rho = 0.866, P < .001) and overall governance scores (rho = 0.828, P < .001). ConclusionBased on the results of this study, we can conclude that well-functioning health center governing boards can improve the performance of health centers against clinical, and management reform standards. Therefore, continuous strengthening of the capacity of governing boards, focusing on improving implementation of their roles and responsibilities, and continuing training on business management is recommended.